2015
DOI: 10.1016/j.celrep.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Fatty Acids Stimulate Tumor Growth through Stabilization of β-Catenin

Abstract: Summary Some cancer cells exhibit elevated levels of free fatty acids (FAs) as well as high levels of β-catenin, a transcriptional co-activator that promotes their growth. Here we link these two phenomena by showing that unsaturated FAs inhibit degradation of β-catenin. Unsaturated FAs bind to the UAS domain of Fas-associated factor 1 (FAF1), a protein known to bind β-catenin, accelerating its degradation. FA binding disrupts the FAF1/β-catenin complex, preventing proteasomal degradation of ubiquitinated β-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 34 publications
2
58
3
Order By: Relevance
“…As Wnt4 did not increase levels of 'active' β-catenin, the increased β-catenin seen with Wnt4 is presumably still phosphorylated by GSK3β, suggest that Wnt4 may disrupt the ubiquitin proteasome pathway or stabilise β-catenin by phosphorylating the protein on a different residue. This GSK3β independent stabilisation of β-catenin has recently been described in tumour cells in response to unsaturated fatty acids in [28].…”
Section: Accepted Manuscriptsupporting
confidence: 53%
“…As Wnt4 did not increase levels of 'active' β-catenin, the increased β-catenin seen with Wnt4 is presumably still phosphorylated by GSK3β, suggest that Wnt4 may disrupt the ubiquitin proteasome pathway or stabilise β-catenin by phosphorylating the protein on a different residue. This GSK3β independent stabilisation of β-catenin has recently been described in tumour cells in response to unsaturated fatty acids in [28].…”
Section: Accepted Manuscriptsupporting
confidence: 53%
“…Intriguingly, the attenuation of FFA1/GPR40 expression by transfecting PC3 cells with the Sh3 construct was able to prevent Akt phosphorylation by OA (Figure ), suggesting that OA induced the PI3K/Akt pathway activation via FFA1/GPR40. It has been recently described that increased FFA levels can affect clear cell renal cell carcinoma proliferation through β‐catenin stabilization (Kim et al, ). However, we did not observe the increase of β‐catenin following OA treatment in our cellular system (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Kwan et al reported the opposite observation, that C16:0 promoted melanoma growth by activating Akt signaling in a phosphatase and tensin homolog–independent manner . On the other hand, unsaturated fatty acid C18:1 was reported to stimulate tumor growth through stabilization of β‐catenin . Other research has provided evidence that C16:0 is lipotoxic and mediates steatohepatitis or nonalcoholic fatty liver disease .…”
Section: Discussionmentioning
confidence: 99%